User study on 3D multitouch interaction (3DMi) and gaze on surface computing - Ch’ng, Eugene; Cooke, Neil (Springer, 2015)
On a multitouch table, user’s interactions with 3D virtual representations of real objects should be influenced by task and their perceived physical characteristics. This article explores the development and user study of an interactive 3D application that allows users to explore virtual heritage objects on a surface device. To-date, most multitouch has focused on 2D or 2.5D systems. A user-study is reported where we analyse their multimodal behaviour – specifically how they interact on a surface device with objects that have similar properties to physical versions and the users’ associated gaze patterns with touch. The study reveals that gaze characteristics are different according to their interaction intention in terms of position and duration of visual attention. We discovered that virtual objects afford the perception of haptic attributes ascribed to their equivalent physical objects, and that differences in the summary statistics of gaze showed consistent characteristics between people and differences between natural and task based activities. An awareness of user behaviours using natural gestures can inform the design of interactive 3D applications which complements the user’s model of past experience with physical objects and with GUI interaction.